Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Scientific Approach Pada Materi Pencatatan Transaksi Keuangan Perusahaan Manufaktur - Farida Sariningtyas; Joni Susilowibowo (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
This development research resulted in a scientific approach based LKPD on the material for recording financial transactions of manufacturing companies at SMKN 1 Jombang which aims to determine the feasibility and responses of students for the development of LKPD. The development model used by researchers is the 4-D (Four D Model) developed by Thiagarajan, including define, design, develop, and disseminate. However in the following research it is only carried out until the develop stage. The instruments used in this study were a closed questionnaire sheet and an open questionnaire sheet. The experts stated the results of the assessment that this development research which was viewed from the point of view of the feasibility of the content and presentation, the feasibility of the language, and the feasibility of the LKPD graphics obtained very good criteria. And the results of student responses to the feasibility of Student Activity Sheets based on a scientific approach in recording manufacturing company financial transactions with very understanding criteria. Thus, student activity sheets based on a scientific approach to recording material for manufacturing company financial transactions are declared very feasible as supporting teaching materials so that they can be used in learning.